Single-text and collected editions to 1623 - Berger, Thomas L; Demetriou, Tania (UK, 2014)
Includes bibliographical references, finding list, and indexes; Volume 1. Single-text and collected editions to 1623 -- volume 2. Single-text and collected editions, 1624-1642
Keywords: English drama -- 17th century -- Criticism; English drama -- Early modern and Elizabethan, 1500-1600 -- Criticism; Paratext; Kịch tiếng Anh -- Thế kỷ 17 -- Phê bình; Kịch tiếng Anh -- Thời cận đại và Elizabethan, 1500-1600 -- Phê bình